Pesticide risks from fruit and vegetable pest management by small farmers in subSaharan Africa: a review - Bon, H. de; Huat, J.; Parrot, L.; Sinzogan, A.A.C.; Martin, T.; Malézieux, E.; Vayssières, Jean-François (Springer, 2014)
Chemical control has highly expanded over the last 30 years in sub-Saharan Africa to reduce bio-aggressors on all crops. Pest management of fruits and vegetables by small farmers in sub-Saharan Africa have developed anarchically in a fuzzy regulation framework. Pesticide toxicity and excessive application are often criticized both by farmers and consumers. Here, we review pesticide management in sub-Saharan Africa over the past 30 years. We then propose options to improve and reduce pesticide application, in order to decrease environmental and human hazards. The major points are as follows: (1) global changes in sub-Saharan Africa such as urbanization modify farmer practices and crop losses. (2) Pesticides aremore and more used by small farmers in an unsustainable way. (3) The risk of pesticide application for human health and environment is poorly known. (4) We propose options to reduce pesticide application based upon integrated pest management (IPM) and agroecology. Moreover, IPM increases farmer economy, thus decreasing poverty.